Dampak Budaya Digital dalam Proses Perancangan Busana - Winwin Wiana (ITB Journal Publisher, LPPM ITB, 2008)
Through times, we may aware that clothes carries more values and meanings than merely covering our 'naked-ness'. In today's world, clothing (or fashion) is representing our identities and associated life-styles. Thus, in today's world clothes has commercial weight as it means big business and financial benefits. The ever-increase competition of today clothing business (especially those of fashion industry) is so fierce that time-to-reach-market becomes priority for clothing-business principals. Many turn into digital technology as it offers product efficiencies and speedy processing. This study discusses the effect of digital culture of today into the process of clothes design.